2007
DOI: 10.1111/j.1365-294x.2007.03423.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow inDubautia arboreaandD. ciliolata: the roles of ecology and isolation by distance in maintaining species boundaries despite ongoing hybridization

Abstract: The relative roles of gene flow and natural selection in maintaining species differentiation have been a subject of debate for some time. The traditional view is that gene flow constrains adaptive divergence and maintains species cohesiveness. Alternatively, ecological speciation posits that the reverse is true: that adaptive ecological differentiation constrains gene flow. In this study, we examine gene flow and population differentiation among populations of two species of the Hawaiian silversword alliance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 78 publications
1
38
1
Order By: Relevance
“…In general, most pollinators visit broader spectra of plants and only few interactions are highly specialised (Goulson, 2003;Levin and Anderson, 1970;Olesen et al, 2002;Waser et al, 1996;Waser, 1998). In accordance with our observations, Friar et al (2007) described the use of generalist pollinators for species of the Hawaiian Silverswords enabling gene flow between them. Despite an overlapping pollinator spectrum, the proportion of infraspecific pollen transfer (averaged 95%) always significantly exceeded the interspecific transfer (3%-21% for specific species pairs).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In general, most pollinators visit broader spectra of plants and only few interactions are highly specialised (Goulson, 2003;Levin and Anderson, 1970;Olesen et al, 2002;Waser et al, 1996;Waser, 1998). In accordance with our observations, Friar et al (2007) described the use of generalist pollinators for species of the Hawaiian Silverswords enabling gene flow between them. Despite an overlapping pollinator spectrum, the proportion of infraspecific pollen transfer (averaged 95%) always significantly exceeded the interspecific transfer (3%-21% for specific species pairs).…”
Section: Discussionsupporting
confidence: 88%
“…Adaptive radiations are defined by species evolving rapidly in response to ecological differences correlating with a burst of morphological and physiological diversity (Schluter, 2000). Given the high tempo of speciation and that the species are closely related, isolation barriers are rather weak or absent and hybridization is generally easy (Francisco-Ortega et al, 2000;Friar et al, 2007;Remington and Robichaux, 2007;Whitkus, 1998). Hence, ongoing interspecific gene flow and hybridization may have an important influence on adaptive radiations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, instances of asymmetric gene flow in hybrid zones are commonly documented in other natural systems [3], including Hawaiian taxa. For example, Friar et al [35] identified ongoing hybridization from Hawaiian Dubautia ciliolata to D. arborea leading to the formation of an active hybrid zone. However, there was little evidence of introgression into parental populations [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Friar et al [35] identified ongoing hybridization from Hawaiian Dubautia ciliolata to D. arborea leading to the formation of an active hybrid zone. However, there was little evidence of introgression into parental populations [35]. Randell et al [41] also found asymmetrical hybridization between Rubus hawaiiensis and R. rosifolius on Maui based on the presence of shared cpDNA haplotypes between the hybrids and R. rosifolius but not R. hawaiiensis .…”
Section: Discussionmentioning
confidence: 99%